The absorption of the variable electric field in superfluid helium by the Аkhiezer mechanism - Naumovets, A.S.; Khodusov, V.D. (Вопросы атомной науки и техники, 2012)
Earlier a series of experiments showed that the energy of a roton in superfluid helium is linearly dependent on electric field. A variable adiabatically changing external electric field leads to a modulation of the roton energy and the absorption of the field by the Akhiezer mechanism. We calculate the absorption of energy, which is resonant at the frequencies of the second-sound waves. Ранее экспериментально было установлено, что энергия ротона в сверхтекучем гелии линейно зависит от электрического поля. Адиабатически изменяющееся внешнее электрическое поле приводит к модуляции энергии ротона и поглощению энергии этого поля по механизму Ахиезера. Вычислено поглощение энергии, которое имеет резонансный характер на частотах волн второго звука. Раніше експериментально було встановлено, що енергія ротонів у надплинному гелії лінійно залежить від електричного поля. Зовнішнє електричне поле, що змінюється адіабатично, призводить до модуляції енергії ротонів і поглинання енергії цього поля за механізмом Ахієзера. Обчислено поглинання енергії, яке має резонансний характер на частотах хвиль другого звуку.